Exploring attitudes and perceptions about the knowledge acquisition process and experiences of Ngangelizwe youth graduates in the Eastern Cape to understand the significance of their education: a Freirean approach - Bango, Yanda Tamsanqeleka (Rhodes University, Faculty of Humanities, Department of Sociology, 2017)
Education is a critical phenomenon which cannot be ignored as its effects cut across all spheres of life, especially the social and economic aspects. In the particular case of South Africa, education has been a serious issue of concern for a very long time and after the transition process took place in 1994 it became a priority on all agendas of governance. Expanding on the already existing debate about education in South Africa, this thesis specifically explores attitudes and perceptions about the knowledge acquisition process and experiences of Ngangelizwe youth graduates to understand the significance of education in their lives. As Freire wrote about the phenomenon of education from the point of view of the oppressed and marginalized in society, his theory explains and aids as a tool for careful analysis in this case. Moreover, considering that at the centre of Freire's world view was the belief that humans have an ontological vocation to become more fully human, the youth graduates of Ngangelizwe became a good case as they live under conditions that one would regard as dehumanizing and oppressive. The youth graduates' actions and attitudes would therefore guide and provide indication as to whether their education, both from academic spaces and the community, has empowered them to challenge the dehumanizing and oppressive nature of the dominant culture as a means to becoming fully human in their life and time, particularly in their community of Ngangelizwe. While the general finding has been that the participants' education portrays both elements of banking and problem-posing education, it was also discovered that it all depends on the level and forces of education that the participants receive their inspiration from. This is due to the fact that education is not one dimensional, it begins from the moment one is born up until he or she no longer exists on earth. Therefore, education does not belong to one group of people; everyone has the ability to educate in as much as he or she has the ability to be educated.
Keywords: Freire, Paulo, 1921-1997; Education -- Sociological aspects -- South Africa -- Mthatha; College graduates, Black -- South Africa -- Mthatha -- Attitudes; College graduates, Black -- South Africa -- Mthatha -- Case studies